Synthesis and Biological Evaluation of Novel Indole Derivatives for Anticancer and Antitubercular Activty - Dixit, Aditya; Pathak, D; Sharma, G. K (Asian Journal of Pharmaceutical Research and Development, 2014)
A series of substituted indole derivatives were synthesized by condensation of 2-(o-Aminophenyl)indole with various benzaldehydes to form N-(Arylidine)-2-(1H indol-2-yl)-benzenamines (2a-2l) which further react with isatin and ammonium acetate to give 3-[2-(1H-Indol-2-yl)phenyl]-2aryl-imidazo[4,5-b]indoles (3a-3l). The synthesized compounds were characterized by FTIR, 1HNMR, mass spectra and elemental analysis. At last, all end products were evaluated for the antitubercular and anticancer activities